Reviving the pedagogy of philosophical inquiry in Muslim curriculum for effective civilizational dialogue - Hashim, Rosnani (2011)
Muslims and Muslim societies are more frequently challenged today by many internal and external threats. Externally they are threatened with globalization, modernity, non-Islamic cultures and values particularly from the West, post-modernity and liberalism and recently to all kinds of Islamophobia. Internally, they are suffering from crisis of values as a result of this onslaught – ranging from gender issues to human rights and democracy. It seems that Muslims encounter a lot of problems in expressing themselves in the contemporary civilizational dialogue. Hence, the purpose of paper is to dissect the problem and argues for a different pedagogical approach in educating the Muslim youth. It is to inform educators that they should incorporate the pedagogy of philosophical inquiry as the necessary tool to awaken, broaden and sharpen the Muslim minds. More importantly, this is returning to the notion of education to liberate men from slavery to men and transforming it to the concern with the brotherhood of men, social justice and moral values.